A rare case of cervical agenesis with agenesis of the upper 2/3rd vagina with hematometra - Makwana, Shailesh; Patel, Manishkumar; Halpati, Sonal (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Cervical agenesis is an extremely rare form of congenital Mullerian anomaly. Due to the rarity of the cases with different presentations ranging from cervical agenesis to dysgenesis (fragmentation, fibrous cord, obstruction of external os), along with the functionality of the uterus, there are numerous conservative surgical options involving uterovaginal anastomosis, cervical reconstruction, and cervical canalization, and total hysterectomy in cases where conservative surgical procedures fail or not feasible. In our case, the patient was a 32-year-old female with primary amenorrhea with, a history of marriage for 6 years and a history of surgery for primary amenorrhea during adolescence. During the present visit, she had severe abdominal pain due to massive hematometra with a short blind vagina. She was planned for laparoscopic Uterovaginal anastomosis but converted to abdominal hysterectomy due to the large size of uterus, lack of uterine supports, and high length of the defect between the lower end of the uterus and vaginal end. Due to the lack of proper guidelines and variations in clinical presentation, a case-based approach is required.